Future of Indian universities : comparative and international perspectives - Kumar, C. Raj
This volume emphasizes the need for fundamental reforms into the existing institutional structure of higher education and their governance so as to infuse much needed dynamism and renewed sense of purpose in the higher education sector in India. The contributors to the volume argue that universities ought to be dynamic institutions where new ideas are exchanged, mistakes made, and lessons learnt. The contributors highlight the fact that the university system in India is based upon a bureaucratic command and control system that constrains the freedom and liberty required for academic pursuit, and disallows flourishing of academic cultures in tandem with the changing demands of India's economy and democracy.
"This volume was inspired by an International Conference on 'The Future of Indian Universities: Comparative Perspectives on Higher Education Reforms for a Knowledge Society' that was held on the campus of the O.P. Jindal Global University (JGU) in 2013"--Acknowledgements.
Includes bibliographical references (pages 438-451) and index.
Keywords: Education, Higher -- India -- Congresses; Universities and colleges -- India -- Congresses; Higher education and state -- India -- Congresses